2-(4-Chlorophenyl)-2-oxoethyl 4-benzamidobenzoate derivatives, a novel class of SENP1 inhibitors: Virtual screening, synthesis and biological evaluation - Chen, Yingyi; Wen, Donghua; Huang, Zhimin; Huang, Min; Luo, Yu; Liu, Bin; Lu, Han; Wu, Yingli; Peng, Yuefeng; Zhang, Jian (Bioorganic & medicinal chemistry letters, 2012)
Chemical structure of 2-(4-chlorophenyl)-2-oxoethyl 4-(3-(benzyloxy)benzamido)benzoate, a Sentrin-specific protease 1 (SENP1) inhibitor. Prostate cancer is one of the most prevalent types of malignant cancers in men and has a high mortality rate among all male cancers. Previous studies have demonstrated that Sentrin/SUMO-specific protease 1 (SENP1) plays an important role in the occurrence and development of prostate cancer, and has been identified as a novel drug target for development of small molecule drugs against prostate cancer. In this paper, we used virtual screening and docking to identify compound J5 as a novel lead compound inhibiting SENP1, from SPECS library. We further investigated the SAR (structure–activity relationship) of the benzoate substituent of compound J5, and discovered compounds 8d and 8e as better small molecule inhibitors of SENP1. Both compounds are the high potent SENP1 small molecule inhibitors discovered up to date, and further lead optimization may lead to a series of novel anti-SENP1 agents. Further SAR studies are in process and will be reported in due course.